U.S. Consumption after the 2008 Crisis - Lee, Jaewoo (IMF Staff Position Notes; Staff Position Note ;, 2010)
U.S. household consumption declined sharply in late 2008, marking a departure from the trend of a steady increase in U.S. consumption as a share of income since the 1980s. Combining econometric and simulation analysis, we estimate that this departure will be sustained beyond the crisis: the U.S. household consumption rate will likely decline somewhat further from its current level, as the saving rate rises to around 6 percent of disposable personal income (from nearly 5 percent in 2009). Compared to the pre-crisis years (2003-07), this saving rate implies a decline in U.S. private-sector demand on the order of 3 percentage points of GDP.